Wood pellets versus pulp and paper: Quantifying the impacts of wood pellets on the pulpwood markets in the southeastern United States. (1st October 2021) - Parajuli, Rajan
Abstract: Since the early 2010s, the production of industrial wood pellet for overseas exports has grown considerably in the Southern United States (U.S.). In order to meet the increasing demand for woody biomass feedstock, the wood pellet mills in the U.S. South consume roundwood pulpwood along with low-valued logging residues and sawmill wood wastes. By estimating empirical roundwood pulpwood market models based on the bi-monthly time-series data, this study estimates the impacts of wood pellet production, precipitation, and the COVID-19 Pandemic on the hardwood and softwood pulpwood stumpage prices in 12 southeastern Atlantic coastal micro-markets. Results suggest that the wood pellet industry has led to an increase in pine pulpwood prices, but no statistically significant impact is found on the hardwood pulpwood prices. Rainfall is found to be a positive determinant of the roundwood pulpwood prices. Furthermore, since March 2020, the COVID-19 Pandemic is estimated to lead about 6% decline in both pine and hardwood pulpwood prices. This study provides empirical evidence and additional insights on the timber market dynamics and how small roundwood markets have reacted to the additional wood demand from a growing bioenergy industry in the U.S. South. Highlights: The wood pellet industry competes with pulp and paper mills for woody biomass. The wood pellet industry has led to an increase in pine pulpwood prices. No significant impact of wood pellets is found on the hardwood pulpwood prices. The COVID-19 Pandemic has led to decline pulpwood stumpage prices.